Developing the GEN-V Startup Ecosystem: An AI-Driven Integration of Multidisciplinary Learning in Vocational High School - Ali Basyah; Waras Kamdi; Purnomo Purnomo; Tuwoso Tuwoso; Razali Hassan (Yayasan Adra Karima Hubbi, 2026)
Background. Traditional vocational education often operates in “silos,” where subjects are taught in isolation, hindering students' ability to integrate diverse competencies into real-world work scenarios. Purpose. This study develops and evaluates the “GEN-V” startup ecosystem an innovative pedagogical model designed to integrate 13 subjects through an AI-driven digital startup project for vocational high school students. Method. Utilizing a Research and Development (R&D) approach with the ADDIE model, this study involved 95 students from three classes (XII DKV 1, 2, and 3) at SMK Negeri 1 Mojokerto, organized into 18 startup teams. Each team was structured into six specialized roles: Chief Executive Officer (CEO), Chief Product Officer (CPO), Chief Marketing Officer (CMO), Chief Financial Officer (CFO), Chief Technology Officer (CTO), and Chief Content Officer (CCO). Data were collected through a centralized project management dashboard, an 8-week startup sprint observation, and multidisciplinary evaluations from a panel of 14 teacher-mentors. Results. The findings demonstrate that the GEN-V ecosystem effectively synchronized multidisciplinary tasks. The “Traffic Light” monitoring system evidenced a 95% task completion rate across all specialized departments. Furthermore, the strategic integration of Google Gemini AI significantly accelerated content production and financial modeling, enabling teams to achieve realistic Break-Even Point (BEP) projections and market validation within a condensed timeframe. Conclusion. The GEN-V ecosystem serves as a transformative learning model that successfully dismantles subject barriers. By fostering AI-human collaboration and disciplined project management, it effectively prepares vocational students for the complexities of the digital startup industry.